Why the military should be interested in biomedical technology : four domains of innovation that could change fighting power - Gisselsson, David; Pirnay, Jean Paul; Wiederoder, Michael; Hart, Corey; Rinaldi, Alberto; Gorgé, Olivier; Iriye, Heather; Carvalho, Luís; Sedlackova, Lucie; Voie, Øyvind; Robinson, Yohan (Biotechnology Advances, 2025)
Biotechnology is a rapidly progressive field, currently transforming agriculture, healthcare, and life sciences. This rapid development comes with serious legal and ethical challenges as well as risks for human security and health. NATO has prioritized biotechnology and human enhancement technologies for defense, focusing on legitimate, defensive applications. This paper highlights four clusters of biomedical technologies with the potential to enhance warfighter performance: 1. Small-scale sensors with response capability: These sensors, already used in civilian healthcare for glucose monitoring and insulin dosing, could be adapted for military use to administer antidotes or antibiotics in response to chemical or biological threats. 2. Microbial engineering: Tailor-made probiotics could prepare soldiers' gut microbiomes to prevent travel-related illnesses, while bacteriophages, can be used to combat infections resistant to antibiotics. 3. Human-machine interaction: Neurocybernetics is transforming military robotics by enabling seamless communication between humans and machines. 4. Omics and informatics: Precision medicine combined with machine intelligence can be used for medical screening and monitoring of soldiers, as well as for biomedical intelligence gathering. These technologies, progressing in civilian sectors, have significant potential to enhance military capabilities in the near future (5–10 years). Oversight and prioritization of human rights are essential to ensure responsible application, maintaining human dignity, bodily integrity, and personal autonomy even in wartime. As military innovation systems worldwide are advancing in strategic biotechnologies, it is critical for NATO countries to maintain synergistic intra-alliance collaboration in this intense field.
Keywords: Biotech; Biotechnology; Defense; Medtech; Military medicine